2021
DOI: 10.3390/cmd2030021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Corrosion Morphology of Duplex Stainless Steel Wire in Chloride Electrolyte

Abstract: The corrosion morphology in grade 2205 duplex stainless steel wire was studied to understand the nature of pitting and the causes of the ferrite phase’s selective corrosion in acidic (pH 3) NaCl solutions at 60 °C. It is shown that the corrosion mechanism is always pitting, which either manifests lacy cover perforation or densely arrayed selective cavities developing selectively on the ferrite phase. Pits with a lacy metal cover form in concentrated chloride solutions, whereas the ferrite phase’s selective cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Micro-galvanic corrosion occurs when the corroding region is active while the remaining part is passive, driven by the oxidation power strength of the electrolyte (and polarization). Such a phenomenon is typical, for example, for duplex stainless steel 24 . In earlier work, it has been shown that the pitting corrosion of duplex stainless steel in diluted chloride solution is pitting, which selectively occurs in the ferrite phase 24,25 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Micro-galvanic corrosion occurs when the corroding region is active while the remaining part is passive, driven by the oxidation power strength of the electrolyte (and polarization). Such a phenomenon is typical, for example, for duplex stainless steel 24 . In earlier work, it has been shown that the pitting corrosion of duplex stainless steel in diluted chloride solution is pitting, which selectively occurs in the ferrite phase 24,25 .…”
Section: Resultsmentioning
confidence: 95%
“…Such a phenomenon is typical, for example, for duplex stainless steel 24 . In earlier work, it has been shown that the pitting corrosion of duplex stainless steel in diluted chloride solution is pitting, which selectively occurs in the ferrite phase 24,25 . The corrosion concentrates more on the entire ferrite phase when the chloride concentration is increased due to more pit nuclei forming next to each other in the ferrite phase.…”
Section: Resultsmentioning
confidence: 95%
“…The intensity of pitting corrosion increases with the temperature of the electrolyte. Mixing the solution equalizes the depolarizers' concentration at the metal surface, thereby slowing the progress of corrosion [41]. A permanent polarization of the cell, i.e., blocking the anode or cathode reaction, may stop the progress of pitting corrosion.…”
Section: Pitting Corrosion Of Stainless Steels Initiated When Exposed To Chloride Impactmentioning
confidence: 99%
“…For this reason, the corrosion and SCC behavior of DSS have been widely studied in the literature. In the case of chloride electrolyte, the preferential phase to dissolve is the α-phase until a threshold chloride concentration is reached (0.1 M NaCl at pH 3 and 60 • C), promoting lacy cover pitting instead in both phases [7,8]. Another focus of previous studies was on the property mismatch between phases such as the mechanical phase, where the α-phase cannot develop as high tensile stresses as the γ-phase [9], and the electrochemical phase, where the α-phase has lower corrosion potential (E corr ) (higher corrosion susceptibility) [10], also leading to galvanic microcouples [11].…”
Section: Introductionmentioning
confidence: 99%